HUBUNGAN KETAHANAN PANGAN DENGAN GIZI KURANG PADA BALITA USIA 2-5 TAHUN (STUDI DI WILAYAH KERJA PUSKESMAS PANGKALAN KABUPATEN LIMA PULUH KOTA) - Hidayati, Hidayati; Margawati, Ani; Noer, Etika Ratna; Syauqy, Ahmad; Kartini, Apoina (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2024)
ABSTRACTBackground: Undernutrition describes acute nutritional status.This situation is presented with a Z-Score value of BB/TB at the of <-3 SD to <-2 SD malnutrition category based on World Health Organization (WHO) standards. One of the factors that causes malnutrition in toddlers is family food security.Objectives: To analyze the relationship between food security and malnutrition in children aged 2-5 years in the PangkalanCommunity Health Center working area.Methods: Observational research using a cross sectional study design. The research was 300 children aged 2-5 years, selected through simple random sampling. Food security was calculated using a questionnaire (HFFSM), as well as anthropometric measurements of BB/TB. Bivariate data analysis was carried out using the Spearman correlation test.Results :As much 75.7% low food security and nutritional status BB/TB malnutrition was 9%. The results of the Spearman correlation test, show that there is a relationship between family food security and nutritional status according to Z-Score BB/TB p-value 0,023 r=0,131*, this means that if the BB/TB score is low, food security will be increasingly dangerous.Conclusion: Family food security is one of the factors that can increase the incidence of underweight in toddlers aged 2-5 years. Nutritional problems are caused by weak family food security, which is the family’s ability to meet the food needs of household members in terms of quantity, quality, and variety according to local culture. Efforts that can be made to increase food security in households so that nutritional intake can be met properly including empowering houdewives regarding how to manage finances for household consumption as well as empowering training such as sewing and managing small and medium household businesses (UMKM).Keywords : Malnutrition; food security; toodlers ABSTRAKLatar belakang: Gizi Kurang menggambarkan status gizi yang bersifat akut, keadaan ini dipresentasikan dengan nilai Z-score BB/TB pada ambang batas <-3 SD sampai dengan <-2 SD kategori gizi kurang berdasarkan standar World Health Organization (WHO). Salah satu yang menjadi faktor terjadinya gizi kurang pada balita yaitu ketahanan pangan keluarga.Tujuan: Menganalisis hubungan ketahanan pangan dengan gizi kurang pada anak usia 2-5 tahun di wilayah kerja Puskesmas Pangkalan.Metode: Penelitian observasional dengan menggunakan rancangan study cross-sectional. Penelitian melibatkan 300 anak usia 2-5 tahun yang dipilih melalui simple random sampling, ketahanan pangan dihitung menggunakan kuesioner (HFFSM) serta pengukuran antropometri berat badan dan tinggi badan.. Analisis data bivariate dilakukan dengan menggunakan uji korelasi spearman. Hasil: Sebanyak 75.7% ketahanan pangan rendah (low food security) dan status gizi BB/TB gizi kurang sebanyak 9%. Hasil uji korelasi spearman menunjukkan terdapat hubungan ketahanan pangan keluarga dengan status gizi menurut Z-Score BB/TB (p=0.023) r=0,131*, artinya apabila skor BB/TB rendah maka ketahanan pangan nya semakin rawan.Simpulan: Kerawanan pangan keluarga merupakan salah satu faktor yang dapat meningkatkan kejadian gizi kurang pada balita usia 2-5 tahun. Masalah gizi disebabkan lemahnya ketahanan pangan keluarga yang merupakan kemampuan keluarga untuk memenuhi kebutuhan pangan anggota rumah tangga dari segi jumlah, mutu dan ragamnya sesuai dengan budaya setempat. Upaya yang dapat dilakukan untuk meningkatkan ketahanan pangan di rumah tangga sehingga asupan gizi dapat terpenuhi dengan baik yaitu pemberdayaan kepada ibu rumah tangga terkait bagaimana pengelolaan keuangan untuk konsumsi rumah tangga serta pemberdayaan pelatihan seperti menjahit dan pengelolaan usaha rumah tangga kecil dan menengah (UMKM).Kata Kunci : Gizi Kurang; Ketahanan Pangan; Balita